2021
DOI: 10.3390/microorganisms9091850
|View full text |Cite
|
Sign up to set email alerts
|

Plant Microbial Biostimulants as a Promising Tool to Enhance the Productivity and Quality of Carrot Root Crops

Abstract: The interest in studies focused on applying probiotic microorganisms is increasing due to sustainable agriculture development. In this research, we aimed to evaluate the impact of two commercial plant probiotics—ProbioHumus and NaturGel on carrot growth, yield, and quality in organic and nonorganic production systems. The research was carried out under laboratory and field conditions. Plants were treated with probiotics (2 L/ha) at the nine leaves stage. Biometrical measurements and chemical analyses were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Bio-inputs applied were based on bacteria such as Bacillus subtilis, Lactobacillus, Saccharomyces cerevisiae yeast, humic and fulvic acids, among other compounds common to the formulations used in this study's experiments, and administered at low doses of 2L/ha. Besides the increase in carrot weight, a greater accumulation of monosaccharides, carotenoids, and phenols and increased antioxidant activity were also observed (Gavelienė et al 2021).…”
Section: Discussionmentioning
confidence: 91%
“…Bio-inputs applied were based on bacteria such as Bacillus subtilis, Lactobacillus, Saccharomyces cerevisiae yeast, humic and fulvic acids, among other compounds common to the formulations used in this study's experiments, and administered at low doses of 2L/ha. Besides the increase in carrot weight, a greater accumulation of monosaccharides, carotenoids, and phenols and increased antioxidant activity were also observed (Gavelienė et al 2021).…”
Section: Discussionmentioning
confidence: 91%
“…are somewhat synonymous with each other and are part of a complex microbial community that either colonizes the rhizosphere (rhizomicrobiome; Ravichandran et al, 2022 ) or diffuse in or localizes in plant tissues (endophytes; Pandey et al, 2022 ; Rai et al, 2023 ) and contribution to beneficial functional traits in favor of plants ( Gosal et al, 2017 ). These beneficial traits include enhancement in plant growth and productivity ( Gavelienė et al, 2021 ), amelioration of abiotic and biotic stresses in plants ( Santoyo et al, 2021 ), lowering the challenges of climate changes effects ( Fiodor et al, 2021 ), and biofortification benefits via improving micronutrients levels in crop edibles ( Upadhayay et al, 2018 , 2021 , 2022a , b , c ). Plant probiotics must contain some PGP traits such as the solubilization of elements (P, K, and Zn; Singh et al, 2022 ), nitrogen fixation ( Pandey et al, 2022 ), production of phytohormones ( Kurniawan and Chuang, 2022 ) aminocyclopropane-1-carboxylate (ACC) deaminase ( Santos et al, 2022 ; Singh et al, 2022 ), siderophore ( Upadhayay et al, 2022a , b ), and ammonia ( Santos et al, 2022 ).…”
Section: Plant Probiotics: Unraveling a Long Story In A Nutshellmentioning
confidence: 99%
“…These microorganisms promote plant growth by converting essential nutrients (mainly nitrogen, phosphorus, and potassium) from non-absorbable to absorbable forms [ 8 , 9 , 10 ]. Several years of research by Gavelienė et al [ 11 ] has shown that microbial biostimulants can have a positive influence not only on yield but also on quality by increasing the amount of nutrients and bioactive compounds present that are beneficial to human health.…”
Section: Introductionmentioning
confidence: 99%